Sri Lanka : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2005)
This Selected Issues paper on Sri Lanka reviews several issues that highlight both Sri Lanka's accomplishments and their policy constraints amidst a protracted period of civil conflict and political instability. High intermediation costs have held back development of the financial sector and could also frustrate Sri Lanka's quest for higher growth. The main constraints to achieving higher growth include the civil conflict, political instability, high fiscal deficits and inflation, and underdeveloped financial markets.